2005
DOI: 10.1681/asn.2004080655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrafiltration on Thermal Variables, Skin Temperature, Skin Blood Flow, and Energy Expenditure during Ultrapure Hemodialysis

Abstract: The cause of the increase in core temperature (CT) during hemodialysis (HD) is still under debate. It has been suggested that peripheral vasoconstriction as a result of hypovolemia, leading to a reduced dissipation of heat from the skin, is the main cause of this increase in CT. If so, then it would be expected that extracorporeal heat flow (Jex) needed to maintain a stable CT (isothermic; T-control ‫؍‬ 0, no change in CT) is largely different between body temperature control HD combined with ultrafiltration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 30 publications
0
43
0
2
Order By: Relevance
“…The resulting increase in CT would then eventually evoke a reflex cutaneous vasodilation, resulting in a sudden decline in BP. However, in a recent controlled study, differences in the thermal response were not observed between dialysis treatments with or without concomitant ultrafiltration, which would appear to contradict the former hypothesis (18). Various studies have shown vasodilation in the forearm or skin blood vessels during "standard" dialysis sessions with T d of 37°C or higher (26,27).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The resulting increase in CT would then eventually evoke a reflex cutaneous vasodilation, resulting in a sudden decline in BP. However, in a recent controlled study, differences in the thermal response were not observed between dialysis treatments with or without concomitant ultrafiltration, which would appear to contradict the former hypothesis (18). Various studies have shown vasodilation in the forearm or skin blood vessels during "standard" dialysis sessions with T d of 37°C or higher (26,27).…”
Section: Discussionmentioning
confidence: 93%
“…Arterial (T art ) and venous (T ven ) blood line temperatures and energy transfer between the extracorporeal circuit and the patient were noninvasively monitored using the BTM device, as described previously (7,13), at 60-s intervals (7,8,17,18). During isothermic, the change in patient temperature was set to zero.…”
Section: Thermal Prescription and Assessmentmentioning
confidence: 99%
“…Overall, the duration of each trial was short. Eighteen trials reported the effect of cool dialysis on the basis of two sessions of hemodialysis (one session in each arm of the trial) (16,17,21,23,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)41). Three trials evaluated the intervention in three to six hemodialysis sessions (22-24).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Using a Laser-based contact skin device in a limited skin area of the palmar part of hands, Van der Sande described skin blood flow change both in isothermic and thermoneutral HD sessions with ultrafiltration, contrary to no change in both thermal regimes of HD without ultrafiltration. [11] To our knowledge, no systematic data about the impact of hemodialysis on the peripheral microvascular blood flow in large surface skin area are available in the literature.…”
Section: E Mistrík Et Almentioning
confidence: 99%